Psychometric Properties Of The Intrinsic Motivation Inventory (Imi) Among Indonesian Student Futsal Athletes - Syahrinda, Yusuf Akbar; Juriana, Juriana; Deasyanti, Deasyanti; Rangkuti, Anna Armeini (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aimed to adapt and validate the Intrinsic Motivation Inventory (IMI) for Indonesian futsal student-athletes within the framework of Self-Determination Theory. A cross-cultural psychometric adaptation process was conducted, including translation, synthesis, back-translation, expert judgment, and field testing. Data were collected from 61 student-athletes, and content validity was assessed using Aiken’s V, yielding a strong result (V = 0.85). The IMI demonstrated good internal consistency (Cronbach’s α = 0.869) and significant interdimensional correlations, such as between perceived competence and enjoyment-interest (r = 0.516, p < .001). The mean intrinsic motivation score (M = 75.84) indicated a moderately high level of motivation among participants. These findings confirm that the adapted IMI is a valid and reliable instrument for measuring intrinsic motivation among futsal athletes in Indonesia. Theoretically, the study supports Self-Determination Theory in a team-sport context, and practically, it provides a culturally relevant tool for coaches and sport psychologists to assess and enhance athlete motivation.